Peripherally Inserted Central Venous Catheter (PICC) Line Use for Conjoined Twins: Single-Center Experience - Elzahrani, Mohamed; Zahrani, Yousof Al; Alqarni, Alwaleed; Alothri, Meshal; Moaiqel, Mohammed Al; Alotaibi, Mohammed; Alzahrani, Amin; Almulhim, Abdulaziz (The Arab Journal of Interventional Radiology, 2024)
Purpose This article assesses the feasibility, safety, and efficacy of peripherally inserted central catheters (PICCs) in conjoined twins.Material and Methods A retrospective chart review of all consecutive conjoined twins who had PICC placement at a tertiary center. Seventeen conjoined twins (12 females; 71%) had 25 PICC insertions. The average age of patients at PICC insertion was 15.9 ± 19.3 months. The most common type of twin was thoraco-omphalopagus (5 patients; 29%). The most common access was the brachial vein (N = 10, 40%). Thirteen procedures (52%) were performed before separation.Results Seven long-term minor complications were identified (28%). The most common complication was malpositioning (8%). Average dwell time was 122 days while the average fluoroscopy time was 2 minutes and 3 seconds.Conclusion Image-guided PICC placement in conjoined twins is safe and feasible. It provides excellent durable vascular access.
Keywords: interventional; peripherally inserted central catheter; thrombosis